Postural effects on intraocular pressure and ocular perfusion pressure in patients with non-arteritic anterior ischemic optic neuropathy - Yang, Jee Myung; Park, Sang Woo; Ji, Yong Sok; Kim, Jaeryung; Yoo, Chungkwon; Heo, Hwan (BMC ophthalmology, 2017)
Background To investigate postural effects on intraocular pressure (IOP) and ocular perfusion pressure (OPP) in patients with non-arteritic ischemic optic neuropathy (NAION). Methods IOP and blood pressure (BP) were measured in 20 patients with unilateral NAION 10 min after changing to each of the following positions sequentially: sitting, supine, right lateral decubitus position (LDP), supine, left LDP, and supine. IOP was measured using a rebound tonometer and OPP was calculated using formulas based on mean BP. The dependent LDP (DLDP) was defined as the position when the eye of interest (affected or unaffected eye) was placed on the dependent side in the LDP. Results IOPs were significantly higher ( P = 0.020) and OPPs were significantly lower ( P = 0.041) in the affected eye compare with the unaffected eye, with the affected eye in DLDP. Compared with the mean IOP of the unaffected eyes, the mean IOP of the affected eyes increased significantly (+2.9 ± 4.4 versus +0.7 ± 3.1 mmHg, respectively; P = 0.003) and the mean OPP decreased significantly (−6.7 ± 9.4 versus −4.9 ± 8.0 mmHg, respectively; P = 0.022) after changing positions from supine to DLDP. In addition, changing position from supine to DLDP showed significantly larger absolute changes in IOP (4.13 ± 3.19 mmHg versus 2.51 ± 1.92 mmHg, respectively; P = 0.004) and OPP (9.86 ± 5.69 mmHg versus 7.50 ± 5.49 mmHg, respectively; P = 0.009) in the affected eye compared with the unaffected eye. In the affected eye, there was a significant positive correlation between absolute change in IOP and OPP when changing position from supine to DLDP (Rho = 0.512, P = 0.021). Conclusions A postural change from supine to DLDP caused significant fluctuations in IOP and OPP of the affected eye, and may significantly increase IOP and decrease OPP. Posture-induced IOP changes may be a predisposing factor for NAION development.